DETERMINAN PENERIMAAN PAJAK PENGHASILAN ORANG PRIBADI DI KPP PRATAMA CIREBON - Yudi Mahadianto; Puji Rahmawati (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2019)
This research aims to test the effect of the taxpayer, tax audit and tax extensification on personal income tax in KPP Pratama Cirebon Satu period 2014-2018. The type of research used is basic research and the type of research based on study objectives is hypothesis testing. The analyses used multiple regression analyses, conducting classical assumption tests, a coherent determination (R2), and hypothesis testing conducted with T (partial) tests. The results of this study indicate that the tax payers and the tax extensification have no effect on the personal income tax while the tax audit affects the personal income tax.